2015
DOI: 10.1159/000371493
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Responses following Brain Injuries and Inflammatory Process Activation Induced by a Neurotoxin of <b><i>Androctonus</i></b> Scorpion Venom

Abstract: Objective: Kaliotoxin 2 (KTX2), a neurotoxin isolated from Androctonus australis hector scorpion venom, presents a high affinity with the voltage-gated potassium channels. The targets of KTX2 in the brain and its toxic effects on the cerebral cortex have been extensively studied; however, its deleterious systemic effects on other organ systems have not yet been investigated. Inflammatory response induced by KTX2 is supported by cytokine release which could provoke multiple orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In addition, when this toxin was subcutaneously injected in rats, it caused an increase in leukocyte rolling and adhesion and high levels of tumoral necrosis factor-α (TNF-α) in the brain [ 14 ]. Moreover, the intracerebroventricular injection of KTX 2 , a toxin isolated from Androctonus australis , caused an inflammatory response in the brain of mice and had consequences on pancreatic and hepatic functions, probably mediated by the release of interleukin-6 (IL-6) and TNF-α [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when this toxin was subcutaneously injected in rats, it caused an increase in leukocyte rolling and adhesion and high levels of tumoral necrosis factor-α (TNF-α) in the brain [ 14 ]. Moreover, the intracerebroventricular injection of KTX 2 , a toxin isolated from Androctonus australis , caused an inflammatory response in the brain of mice and had consequences on pancreatic and hepatic functions, probably mediated by the release of interleukin-6 (IL-6) and TNF-α [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The voltage‐gated potassium channels play an important role in diverse physiological processes including the neuronal excitability regulation, neurotransmitter release, and hormone secretion .The potassium channel blockers diversity and their pharmacological specificity enable them to be excellent tools to study some neurological processes. KTX was able to induce severe disturbances in CNS followed by systemic responses . KTX ability to induce thyroid hormones’ synthesis and their release in serum could be attributed to its capacity to stimulate the hypothalamic–pituitary axis since it was able to increase the ROS release leading to an oxidative stress development which could be responsible of the observed tissue damage of hypothalamus and thyroid and the hormone release .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, previous studies have reported that KTX, injected by i.c.v. route, induced severe alterations on structure and functions of central and peripheral nervous systems associated to an immuno‐inflammatory response . Moreover, these studies showed also that the activation and the release of inflammatory mediators (cytokines, reactive oxygen species, and nitric oxide) may play a crucial role in the pathophysiology of the toxicity and may be responsible of the inflammatory manifestations and organ failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The α-KTx Ts6 induced NO and IL-6 production and inhibited the release of TNF-α [ 17 ]. Kaliotoxin 2 (KTX 2 ), an α-KTx from Androctonus australis hector scorpion venom, induces severe alterations in hepatic and pancreatic tissues by the activation of the inflammatory response with release of IL-6 and TNF-α [ 32 ]. However, there is no previously published study on the effect of β-KTx on macrophages.…”
Section: Discussionmentioning
confidence: 99%